Ionized magnesium levels and atrial fibrillation in patients undergoing cardiac surgery – The iMagic Prospective Cohort Study - Mahan Sadjadi; Thilo von Groote; Sina Krone; Ludwig Maximilian Schöne; Christian Strauss; Moritz J. Mertes; Christine Martin; Felix Dinkel; Jessica Schellnack; Thomas Fraune; Carola Wempe; Alexander Zarbock; et al. (PLoS ONE, 2026)
Background New-onset atrial fibrillation (AF) after cardiac surgery is associated with unfavorable outcomes. Electrolyte imbalances have been described as potential risk factors. The effects of ionized magnesium (iMg), a component of total magnesium (tMg) concentration in the blood, and the influence of iMg-dynamics on the incidence of postoperative atrial fibrillation (POAF) are unclear. Methods Ionized Magnesium Levels and Atrial Fibrillation in Patients undergoing Cardiac surgery (iMagic) was a single-center prospective cohort study. A total of 200 patients were enrolled over six months. Plasma-iMg and -tMg levels were measured at different time points in patients without pre-existing AF undergoing on-pump cardiac surgery. The primary outcome was the incidence of POAF. Results Of 200 participants, 55 (27.5%) developed new-onset POAF. Ionized magnesium levels at five pre-specified time points did not vary significantly between patients who later developed POAF and those who did not. Exploratory analyses showed a trend toward higher postoperative iMg, but not tMg (0.78 mmol/L, standard deviation [SD] 0.1 vs. 0.74 mmol/L, SD 0.11, P = 0.096) in patients who developed POAF. This exploratory finding was more pronounced in patients who underwent isolated coronary artery bypass graft (CABG) surgery, and at certain time points, including anesthesia induction (mean iMg 0.71 mmol/L, SD 0.11 vs. 0.65 mmol/L, SD 0.07, P = 0.05). Conclusions Plasma-iMg levels did not vary between cardiac surgery patients who developed POAF and those who did not. Exploratory subgroup analyses indicated that iMg-levels may be associated with POAF in patients undergoing isolated CABG surgery. Perioperative measurement of iMg in patients at risk of POAF undergoing isolated CABG surgery may be beneficial, but more data are needed to support our preliminary findings. The risk factors for dysmagnesemia and subsequent patient-centered outcomes, such as new-onset POAF, have yet to be described for cardiac surgery.